Applied improvisation and transdisciplinary simulation: a necessity for any health curriculum? - De Wever, Julie; Hainselin, Mathieu; Gignon, Maxime (Frontiers in Medicine, 2023)
From practising a procedure, such as a lumbar puncture, to explaining the aim and method and listening to concerns, the practice of health professionals requires a range of skills, often classified into technical and non-technical skills. Just as gestures and procedures can be taught, so can empathy and communication skills. This article introduces an innovative approach that unites both necessary types of skills. The specific framework of improvisational theatre (“improv”) has widespread application, including the training of health professionals (health training improv). By sharing close contexts and skills, health training improv provides a valuable, safe, and effective learning environment that allows practitioners to practice exercises and situations that align with particular objectives. We created a transdisciplinary team to develop a programme of Health Professional Training Improv (HPTI), bringing together the fields of health, psychology, simulation, and arts. Since 2019, various health student groups (nurses, midwives, medical doctors, and speech therapists) have participated in a 16-h applied improv training workshop under the supervision of a professional improv facilitator. Additionally, drama students completed applied improv for health courses, which trained them to act as simulated patients, with a view to the implementation of transdisciplinary improv simulation sessions at SimUSanté (a multidisciplinary health simulation facility located in France). Students’ feedback emphasized their interest in HPTI, the realism of the simulation sessions, and the skills they felt had improved. This feedback needs to be supplemented with quantitative data from standardised assessments. The development of this rich pedagogical and research framework, based on a transdisciplinary approach, has brought different fields together to prepare students for real patient encounters. It is essential to continue this training and conduct research to evaluate the curricula developed.